Development of Marriage Preparation Inventory: Validity and Reliability from Rasch Perspective - Esti Wulandari; Herman Nirwana; Afdal Afdal (Indonesian Institute for Counseling, Education and Therapy (IICET), 2020)
One of the factors that causes divorce among Indonesians is the physical and psychological unpreparedness of the bride and groom. The purpose of this study was to validate the Psychological Readiness instrument for psychological conditions that affect the prospective bride and groom to carry out a marriage developed using the theory of Fowers & Olson (1989). Validation of this instrument needs to be done because there is no instrument that can truly represent the psychological conditions of the bride and groom, although there are still separate variables. So the importance of developing valid and reliable instruments. The research sample consisted of 40 prospective brides who attended marriage guidance in the city of Padang, then analyzed using Rasch. The results showed that the psychological readiness instrument was valid and reliable with the person reliability 0.84 and the item reliability 0.89.